Representation and participation in child care proceedings: what about the voice of the parents?. Issue 3 (2nd July 2016) - O'Mahony, Conor; Burns, Kenneth; Parkes, Aisling; Shore, Caroline
Abstract: In Ireland, the Constitution guarantees very strong rights to parents and the family, and there has been a long and unfortunate history of failures to adequately protect children at risk. As a result, there has been much discussion in recent years about the need to improve legal mechanisms designed to protect the rights of children. By comparison, little attention has been given to establishing whether the theoretically strong rights of parents translate into strongly protected rights in practice. This paper presents new empirical evidence on the manner in which child care proceedings in Ireland balance the rights and interests of children and parents, including the rates at which orders are granted, the frequency of and conditions in which legal representation is provided, and the extent to which parents are able to actively participate in proceedings. A number of systemic issues are identified that restrict the capacity of the system to emphasise parental rights and hear the voice of parents to the extent that would be expected when looking at the legal provisions in isolation.